2005
DOI: 10.1577/m04-102.1
|View full text |Cite
|
Sign up to set email alerts
|

A Long‐Term Comparison of Redband Trout Distribution, Density, and Size Structure in Southwestern Idaho

Abstract: During 1993During -2003, we reexamined the density and size structure of populations of Columbia River redband trout Oncorhynchus mykiss gairdneri at 43 sites in sagebrush desert basins of southwestern Idaho. Trout density had originally been sampled at these sites during 1977-1982. Populations were sampled in four major drainages of the Snake River basin: Bruneau River, Jordan Creek, Owyhee River, and Snake River tributaries. Redband trout distribution remained relatively stable between the two time periods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Zoellick et al (2005) determined that the mean density of selected desert populations of redband trout remained similar in southern Idaho desert streams between the 1970s and 1990s. Redband trout residing in remote desert streams have little fishing pressure and mortality rates are well below those for stocks in more accessible montane environments (Schill et al 2007).…”
mentioning
confidence: 99%
“…Zoellick et al (2005) determined that the mean density of selected desert populations of redband trout remained similar in southern Idaho desert streams between the 1970s and 1990s. Redband trout residing in remote desert streams have little fishing pressure and mortality rates are well below those for stocks in more accessible montane environments (Schill et al 2007).…”
mentioning
confidence: 99%
“…Mean summer water temperature, streamflow, habitat complexity, substrate composition, and stream shading have all been identified as important factors in determining habitat quality. In desert streams, several studies have shown that stream-shading bank cover and stability, substrate composition, and habitat connectivity are important habitat features in the distribution and abundance of Redband Trout (Zoellick 1999(Zoellick , 2004Zoellick et al 2005;Zoellick and Cade 2006;Meyer et al 2010). Water temperature, which has direct effects on the physiology, behavior, and ecological interactions of Redband Trout (Cassinelli and Moffitt 2010;Feldhaus et al 2010;Kammerer and Heppell 2013), has been identified as an important determinant of habitat quality across a wide range of environmental conditions, especially in hot, arid rangeland basins.…”
Section: Status and Conservation Of Interior Redband Troutmentioning
confidence: 99%
“…Land development activities such as road construction, logging, and grazing can alter substrate composition and reduce the frequency and area of pools, which are critical to Redband Trout in the headwaters of the Columbia River basin in Montana and Idaho (Muhlfeld et al 2001a(Muhlfeld et al , 2001bMuhlfeld 2002). Many desert populations of interior Redband Trout are threatened by the degradation of stream and riparian habitat and the increased water temperatures resulting from grazing and agricultural practices (Zoellick 2004;Zoellick et al 2005;Zoellick and Cade 2006;Johnson and Fite 2007;Bayley and Li 2008). Artificial barriers have isolated many Redband Trout populations and eliminated habitats that were previously available to migratory populations (Thurow et al 2007;Holecek et al 2012;Holecek and Scarnecchia 2013).…”
Section: Threatsmentioning
confidence: 99%
“…In the desert region, elevations range from 750 to 2,560 m and the landscape is predominately vegetated with sagebrush Artemesia spp. in the lower elevations and western juniper Juniperus occidentalis and Douglas-fir Pseudotsuga menziesii in the higher elevations (Zoellick et al 2005). Maximum stream temperatures typically fluctuate from 18 • C to 26 • C during the summer months but have been recorded as high as 30-32 • C in some reaches (Zoellick 1999;Meyer et al 2010).…”
mentioning
confidence: 99%